Effects of diet substitution on growth performance, energy consumption and digestive enzymes in Macrobrachium rosenbergii postlarvae - Radhakrishnan S.; Saravana Bhavan P.; Seenivasan C; Muralisankar T. (Advances in Aquaculture and Fisheries Management, 2015)
The present study was conducted to assess the growth promoting ability of Chlorella vulgaris on Marobrachium rosenbergii postlarvae. The experimental diets were prepared by fishmeal replacement with C. vulgaris at different levels (25, 50, 75 and 100%). The prepared feeds were offered to the M. rosenbergii postlarvae during 90 days in triplicate. At the end of the feeding experiment, survival rate, weight gain, specific growth rate and feed conversion efficiency were significantly (P < 0.05) higher in 50% C. vulgaris inclusion diet fed PL group. Similarly, total protein, amino acid, carbohydrate and lipid contents were significantly (P < 0.05) higher in specimens fed 50% C. vulgaris supplemented diet. The feeding rate, absorption rate, conversion rate were significantly (P < 0.05) higher in 50% C. vulgaris supplemented diet fed PL group. At this level of replacement, the activity level of digestive protease, amylase and lipase were significantly (P < 0.05) higher in 50% C. vulgaris supplemented group. Among all the experimental groups, the 50% fishmeal replacement with C. vulgaris inclusion diet fed group, showed significant performance. The present results revealed that the partial replacement of fish meal with C. vulgaris is favorable for M. rosenbergii postlarval culture.